Spatial modelling for nitrogen leaching from intensive farming in Red River Delta of Vietnam - Mai, V.T.; Hoanh, Chu Thai; Keulen, H. van; Hessel, R. (2013)
In this study, a spatial dynamic model was developed, to simulate nitrogen dynamics in Van Hoi commune, Tam Duong district, Vietnam, for different soil and land use types, under different irrigation and fertilizer regimes. The model has been calibrated using measured nitrogen concentrations in soil solution in March and August 2004 and validated for data from March and August 2005. Lateral flow was low in this level area. Percolation was the main process leading to high nitrogen leaching losses to ground water. Calculated annual leaching losses varied from 88 to 122 kg N ha-1 in flowers, 64 to 82 in vegetables of the cabbage group, 51 to 76 in chili, 56 to 75 in vegetables of the squash group, and 36 to 55 in rice.